Math, asked by himanshukumarnirala, 1 year ago

please solve question no. 15 urgent me

Attachments:

Answers

Answered by Anonymous
0

hi!

(2z - 7) - 3(3z + 8) = 4z - 9

= 2z - 7 - 9z - 24 = 4z - 9

= 2z - 9z - 4z = 24 + 7 - 9

= 2z -13z =31 - 9

= -11z = 21

= -z = 21/11

= z = -21/11

thats the answer......if helped..pl mark the brainliest!


shavin: wron h yrrr
shavin: u r wrong
shavin: 31-9=22
shavin: correct the calculation
shavin: yesssss
Answered by shavin
0
2z-7-9z-24=4z-9
-22=4z-2z+9z
-22=11z
z= -2

shavin: if my answer right mark me as brainlist
shavin: thanks
Similar questions